2021
DOI: 10.52586/5056
|View full text |Cite
|
Sign up to set email alerts
|

Role of misfolding in rare enzymatic deficits and use of pharmacological chaperones as therapeutic approach

Abstract: Introduction 3. Protein misfolding and human disease 4. Use of pharmacological chaperones as therapeutic approach in rare enzymatic deficits 4.1 Gaucher disease 4.2 Phenylketonuria 4.3 Primary hyperoxaluria type I 5. Conclusions 6. Author contributions 7. Ethics approval and consent to participate 8. Acknowledgment 9. Funding 10. Conflict of interest 11. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 163 publications
(210 reference statements)
0
7
0
Order By: Relevance
“…Even minimal increases in membrane localization and function could be sufficient to maintain systemic carnitine levels ( 42 ). Such therapeutic approaches have been successful for CFTR in cystic fibrosis ( 43 ), clinically tested for enzyme deficiencies ( 44 ), and explored for norepinephrine, dopamine, and serotonin transporters NET/ SLC6A2 , DAT/ SLC6A3 , and SERT/ SLC6A4 ( 45 ). In the event that a pharmacochaperone is developed for OCTN2, we envision subcellular localization data to be informative in personalized medicine to identify patients harboring mislocalized variants that may benefit from such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even minimal increases in membrane localization and function could be sufficient to maintain systemic carnitine levels ( 42 ). Such therapeutic approaches have been successful for CFTR in cystic fibrosis ( 43 ), clinically tested for enzyme deficiencies ( 44 ), and explored for norepinephrine, dopamine, and serotonin transporters NET/ SLC6A2 , DAT/ SLC6A3 , and SERT/ SLC6A4 ( 45 ). In the event that a pharmacochaperone is developed for OCTN2, we envision subcellular localization data to be informative in personalized medicine to identify patients harboring mislocalized variants that may benefit from such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The main hallmark of PHs is the increased urinary excretion of oxalate that precipitates as calcium oxalate stones leading to urolithiasis and nephrocalcinosis, eventually causing renal failure and progressing to systemic oxalosis [ 4 ]. This review provides an up-to-date summary on the molecular pathogenesis of PHs, whose investigation has been extremely flourishing in the last years, driven by increased disease awareness, easier access to genetic diagnosis, and availability of new therapeutics [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 PCs used to treat diseases due to enzymatic deficits are either vitamin derivatives functioning as coenzymes or competitive inhibitors of the disease-causing enzyme. 20 22 These molecules are usually characterized by a high binding affinity and specificity, two features that allow them to be effective at a very low concentration. In a proof-of-concept study, we showed that an AGT inhibitor acting as PC is aminooxyacetic acid (AOA).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and cell biology studies performed in the past few years have highlighted that many mutations cause folding defects in AGT that in turn can determine (i) increased aggregation tendency, either in the cytoplasm or inside peroxisomes; (ii) reduced stability of the dimeric structure of the protein, typically in the apo-form; (iii) enhanced susceptibility to proteolytic degradation; and (iv) mistargeting of the protein to mitochondria. Among the approaches under investigation to treat protein misfolding diseases, one of the most promising involves the use of pharmacological chaperones (PCs). PCs are drug-like molecules able to specifically bind a misfolded protein and improve its folding efficiency, thus recovering the intracellular yield of variants affected by conformational defects. , PCs used to treat diseases due to enzymatic deficits are either vitamin derivatives functioning as coenzymes or competitive inhibitors of the disease-causing enzyme. These molecules are usually characterized by a high binding affinity and specificity, two features that allow them to be effective at a very low concentration. In a proof-of-concept study, we showed that an AGT inhibitor acting as PC is aminooxyacetic acid (AOA) .…”
Section: Introductionmentioning
confidence: 99%